Student Perception of the Practical Exam of Introduction to the Clinic in Fourth Semester Medical Students - Yadir López Peña; Zulema Ávila González (PT. Riset Press International, 2026)
Teaching semiotics in healthy patients is the primary objective of the Introduction to Clinical Practice course. This course is a cornerstone of early medical training, enabling students to acquire the skills and abilities to perform a complete, objective, and organized physical examination—an indispensable competency for future healthcare professionals. The objective of this study is to evaluate the perceptions of fourth-semester medical students regarding the Introduction to Clinical Practice Practical Exam. A descriptive, cross-sectional, and analytical study was conducted in March 2025. Descriptive analyses of frequencies, percentages, means, and standard deviations were performed. Forty-two valid responses were analyzed. Most items received scores above 70% in the